Perspektif Hukum Gereja Tentang Kepemimpinan Kolegial-Partisipatif Dalam Gereja Partikular - Rikardus Jehaut (STIPAS St. Sirilus Ruteng, 2020)
This article is primarily focussed on participatory-collegial leadership. The principal objective is to offer a canonical analysis and practical reflections on that kind of leadership within the particular Church. To achieve this objective, the article is developed in four parts. The first, serves as a point of departure, examines the fundamental equality and dignity of the Christian existence of all the members of the People of God, and in their own way share the priestly, prophetic, and kingly office of Christ, and to the best of their ability carry on the mission of the whole Christian people in the Church and in the world. From this essential theological basis, the second part deals with the question of participatory-collegial leadership within the context of relationship between lay people and clergy as well as between diocesan bishop and clergy. The third part is a critical evaluation of the question on the participatory-collegial leadership in daily life with contemporary challenges and what should be thought of in the future as the way forward. The author argues that each member of the lay faithful, together with ordained ministers, shares a responsibility for the Church’s mission by exercising their sharing together in the priestly, prophetic and royal office of Christ towards a dialogical, participatory and co- responsible church. To make this a reality, it is obvious that what so called participatory-collegial leadership must exist in the daily praxis of the church and not top-down, authoritarian, dominative one.